প্রীতি নিন সকলে - রহমান, সিরাজুর. (ঢাকা : ইউনিভার্সিটি প্রেস, 1993)
Autobiographical reminiscences, chiefly on the political developments and social conditions in Bangladesh since 1947.
In Bengali.
Keywords: রহমান, সিরাজুর.; Bangladesh -- Politics and government; Bangladesh -- Social conditions